Genome-wide association study confirms lung cancer susceptibility loci on chromosome 5p15 and 15q25 in an African-American population - Zanetti, Krista A. (Lung Cancer, 2016)
OBJECTIVES: Genome-wide association studies (GWAS) of lung cancer have identified regions of common genetic variation with lung cancer risk in Europeans who smoke and never-smoking Asian women. This study aimed to conduct a GWAS in African Americans, who have higher rates of lung cancer despite smoking fewer cigarettes per day when compared with Caucasians. This population provides a different genetic architecture based on underlying African ancestry allowing the identification of new regions and exploration of known regions for finer mapping. MATERIALS AND METHODS: We genotyped 1,024,001 SNPs in 1737 cases and 3602 controls in stage 1, followed by a replication phase of 20 SNPs (p<1.51×10(−5)) in an independent set of 866 cases and 796 controls in stage 2. RESULTS AND CONCLUSION: In the combined analysis, we confirmed two loci to be associated with lung cancer that achieved the threshold of genome-wide significance: 15q25.1 marked by rs2036527 (p = 1.3 × 10(−9); OR = 1.32; 95% CI = 1.20–1.44) near CHRNA5, and 5p15.33 marked by rs2853677 (p = 2.8 × 10(−9); OR = 1.28; 95% CI = 1.18–1.39) near TERT. The association with rs2853677 is driven by the adenocarcinoma subtype of lung cancer (p = 1.3 × 10(−8); OR = 1.37; 95% CI = 1.23–1.54). No SNPs reached genome-wide significance for either of the main effect models examining smoking - cigarettes per day and current or former smoker. Our study was powered to identify strong risk loci for lung cancer in African Americans; we confirmed results previously reported in African Americans and other populations for two loci near plausible candidate genes, CHRNA5 and TERT, on 15q25.1 and 5p15.33 respectively, are associated with lung cancer. Additional work is required to map and understand the biological underpinnings of the strong association of these loci with lung cancer risk in African Americans.